2021
DOI: 10.33425/2639-9326.1090
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Peripheral Arterial Disease in Type 2 Diabetic Out Patients in A Care Center in Cotonou

Abstract: Aim: To determine the prevalence of peripheral arterial disease and its risk factors in type 2 diabetic outpatients. Materials and Methods: It was a descriptive and analytical cross-sectional study, which included 146 diabetic out patients seen. Peripheral arterial disease (PAD) has been accessed using Ankle-Brachial Index and Arterial Doppler Ultrasound . PAD was defined by an ABI value ≤ 0.9 in either of the legs Data management and analysis were performed using Epi-Info software. A p value <0.05 was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In an Indian study, the prevalence was 36% in diabetics. A higher prevalence (62.3%) was estimated in diabetic patients by Gninkoun et al 20 .Recent results from the Bypass Angioplasty Revascularisation Investigation in type 2 diabetes (BARI 2D) study revealed that a 1% increase in HbA1c was associated with a 21% increased risk of PAD in type 2 diabetics 28 .Moussio et al, noted an increase in HbA1c levels in type 2 diabetics with PAD 29, 30 .Our findings highlighted higher levels of FBG, TC, TG and LDL in the presence of PAD We found a strong and significant positive association between HbA1c and FBG (r = 0.753, p<0.001) and a weak and significant positive correlation between Hba1c and TG (r = 0.288, p<0.001). However, a negative correlation was found with HDL (r= -0.356, p<0.001).…”
Section: Discussionmentioning
confidence: 84%
“…In an Indian study, the prevalence was 36% in diabetics. A higher prevalence (62.3%) was estimated in diabetic patients by Gninkoun et al 20 .Recent results from the Bypass Angioplasty Revascularisation Investigation in type 2 diabetes (BARI 2D) study revealed that a 1% increase in HbA1c was associated with a 21% increased risk of PAD in type 2 diabetics 28 .Moussio et al, noted an increase in HbA1c levels in type 2 diabetics with PAD 29, 30 .Our findings highlighted higher levels of FBG, TC, TG and LDL in the presence of PAD We found a strong and significant positive association between HbA1c and FBG (r = 0.753, p<0.001) and a weak and significant positive correlation between Hba1c and TG (r = 0.288, p<0.001). However, a negative correlation was found with HDL (r= -0.356, p<0.001).…”
Section: Discussionmentioning
confidence: 84%